GIs in Germany : the social, economic, cultural, and political history of the American military presence - Maulucci, Thomas W. Jr. 1966- Herausgeber; Junker, Detlef, Herausgeber; Deutsches Historisches Institut Washington DC (Publications of the German Historical Institute, 2013)
"The fifteen essays in this volume offer a comprehensive look at the role of American military forces in Germany. The American military forces in the Federal Republic of Germany after WWII played an important role not just in the NATO military alliance but also in German-American relations as a whole. Around twenty-two-million US servicemen and their dependants have been stationed in Germany since WWII, and their presence has contributed to one of the few successful American attempts at democratic nation building in the twentieth century. In the social and cultural realm the GIs helped to Americanize Germany, and their own German experiences influenced the US civil rights movement and soldier radicalism. The US military presence also served as a bellwether for overall relations between the two countries"--(Provided by publisher.)